Talent Management in Industry 4.0: A Bibliometric Review of Required Skills and Competencies - Loso Judijanto; Titin Endrawati; Ely Ibrahim; Hesri Mintawati (West Science Interdisciplinary Studies, 2024)
This bibliometric study systematically analyzes the evolving field of talent management within the context of Industry 4.0, employing VOSviewer for mapping and visualizing key research themes, collaborations, and temporal trends from 2012 to 2024. The analysis revealed distinct thematic clusters focusing on the integration of digital transformation within traditional HR practices, emphasizing core competencies, firm capabilities, and the evaluation of job performance. Temporal trends indicate a shift from foundational topics to more complex issues such as leadership competencies and the strategic implications of digital technologies. Density visualizations highlighted areas with heavy research concentration and potential gaps, suggesting opportunities for future studies particularly in emerging and less explored themes. The co-authorship analysis provided insights into collaborative networks, indicating a mix of well-established research groups and emerging scholars. This study not only maps the current landscape but also guides future research directions in talent management amidst rapid technological advancements.